Distortion of the substructure of a 20-ft shipping container exposed to zinc hot-dip galvanizing - Ivanović, Ivana (Materiali in tehnologije, 2013)
The main goal of this study was to build a model for a numerical simulation of hot-dip galvanizing of a 20-ft ISO shipping container. For that purpose, the basic transient thermo-mechanical problem of a steel structure under the influence of the temperature characteristic for a zinc hot-dip galvanizing bath was analyzed. Numerical calculations were performed for a simple part and for the complex substructure of the container. Calculations were carried out on the Salome-Meca platform using a Netgen mesh generator and a Code_Asterfinite-element solver.
Keywords: vroče potopno cinkanje; transportni kontejner; konstrukcijsko jeklo; prenos toplote; deformacije